Mediation in armed conflicts. The experience of the association of rural workers of carare (ATCC) - Hernández Delgado, Esperanza (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article is a research product for peace, it aims at analyzing from the theory of Peace Studies the mediation experience of the Carare Peasant Workers Association (ATCC from Spanish version) in the Colombian internal armed conflict. Its novelty rests in approaching a mediation carried out by a peasant community, involved in this conflict, given its involvement by it; and collect a genuine mediation model generated by the ATCC. The Participant Action Research (PAR) was the method implemented and it was supported by a fieldwork strategy that allowed for in situ observation and semi-structured interviews with relevant participants. Conclusion ATCC teaches an innovative method of community mediation, the importance of internal and involved mediators and the scope of this mediation in internal armed conflicts.